The Effect of the Fraud Hexagon Model on Fraudulent Financial Reporting in State-Owned Enterprises - Meyrani, Hanna; Ramadhan, Yanuar; Munandar, Agus; Wahyuni, Endah Sri (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Fraud cases in Indonesia are largely “dominated by state-owned enterprises (SOEs), ironically, these state-owned enterprises are agents of development and drivers of national economic growth (Sari et al., 2023). The purpose of this study is to analyze the influence of the hexagon theory on detecting fraud in the financial reporting of SOEs listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. The research methodology used was a quantitative method with multiple linear regression analysis. The results of this study indicate that pressure, rationalization, and collusion have a positive effect on the risk of fraudulent financial reporting. Meanwhile, opportunity, capability and ego factors do not have a positive effect on fraudulent financial reporting. It is recommended that future research combine quantitative and qualitative methods to obtain a comprehensive picture of the measurement of the six hexagon elements that are risk factors for fraudulent financial reporting. Future research can also analyze the measurement of independent variables in more depth. Furthermore, it is recommended to find other measurements for variables that, based on the results of this study, do not have an influence on fraudulent financial reporting. The contribution of this research to companies is that companies can map the risk factors for fraudulent financial reporting so that they can take preventive measures by implementing a code of conduct. Furthermore, stakeholders should be more discerning in their response to audit opinions received by companies.